Psalm 104 in the Early Monarchy? revisiting author and date - Pistorius, H. G. (Journal for Semitics, 2019)
Akhenaten used a centralised cult and monolatrism to achieve political stability in Egypt. Hammurabi used Marduk as chief deity in Babylonia to centralise power and create political and religious stability in his kingdom. It is within this ancient Near Eastern tradition of using religion and one specific deity to achieve political stability that Psalm 104 finds its origins. The early Israelite monarchy found itself amidst uncertain political circumstances. The early kings used a centralised monarchy and monolatrism to achieve economic and political stability. The early Israelite government also used other Egyptian influences including governing methods, policies and the use of Egyptian scribes. The monarchy used cultic staff to communicate theologically sanctioned politics. Contact between Egyptian scribes and this cultic staff influenced by Canaanite heritage probably led to the production of a culturally diverse Psalm 104.
free
Keywords: Aten; Baal; Psalm 104